A Somatic Movement Approach to Fostering Emotional Resiliency through Laban Movement Analysis - Tsachor, Rachelle P.; Shafir, Tal (Frontiers in Human Neuroscience, 2017)
Although movement has long been recognized as expressing emotion and as an agent of change for emotional state, there was a dearth of scientific evidence specifying which aspects of movement influence specific emotions. The recent identification of clusters of Laban movement components which elicit and enhance the basic emotions of anger, fear, sadness and happiness indicates which types of movements can affect these emotions (Shafir et al., 2016), but not how best to apply this knowledge. This perspective paper lays out a conceptual groundwork for how to effectively use these new findings to support emotional resiliency through voluntary choice of one’s posture and movements. We suggest that three theoretical principles from Laban Movement Analysis (LMA) can guide the gradual change in movement components in one’s daily movements to somatically support shift in affective state: (A) Introduce new movement components in developmental order; (B) Use LMA affinities-among-components to guide the expansion of expressive movement range and (C) Sequence change among components based on Laban’s Space Harmony theory to support the gradual integration of that new range. The methods postulated in this article have potential to foster resiliency and provide resources for self-efficacy by expanding our capacity to adapt emotionally to challenges through modulating our movement responses.